Large Increase in Dissolved Inorganic Carbon in the East Sea (Japan Sea) From 1999 to 2019 - Na, Taehee; Hwang, Jeomshik; Kim, So-Yun; Jeong, Seonghee; Rho, TaeKeun; Lee, Tongsup (Frontiers in Marine Science, 2022)
The East Sea (also known as the Japan Sea; hereafter, EJS) has its own deep overturning circulation, that operates over a centurial timescale compared with a millennial timescale in the ocean. This allows the EJS to be used as a natural laboratory for investigating potential future changes in the oceanic system. Dissolved inorganic carbon (DIC), total alkalinity (TA), and pH were measured in 2019 in a wide area of the EJS to investigate the characteristics and changes of the carbonate system since the last extensive survey in 1999. In the layer below ∼1,000 m, DIC and apparent oxygen utilization (AOU) was uniform implying rapid horizontal mixing within a few years. Since 1999, DIC concentration increased by ∼11 μmol kg–1 in the layer deeper than 500 m. This increase accompanied a commensurate increase in AOU with the canonical ratio of 1.3, indicating that the accumulation of DIC was supplied from organic matter decomposition. This observation is consistent with a previous study suggesting that the slowed deep water ventilation was the cause of the increase in AOU and fast acidification. In the EJS, increase in DIC from the surface water to deep waters is much higher than that in TA, which is caused by high primary productivity and export production together with low rates of CaCO3 export. Thus, the DIC/TA ratio of deep waters, an indicator of vulnerability to acidification, is high. A recently reported change in deep water ventilation, namely, re-initiation of deep water formation reaching deeper depths to the Deep Water and the Bottom Water, implies that unexpected changes in the carbonate system may be detected in the future, which needs to be further monitored.